Mangement Of Incidental durotomy during the Lumbar Disc Operations - علي, محمد (Latakia University Journal -Medical Sciences Series, 2022)
The study included 1173 patients who underwent lumbar disc excision. The dura mater was ruptured in 5,8% of them. The percentage of males was 50.7%, while the percentage of females was 49.3%. The patients were divided into three groups according to the technique of closure of the dura mater Group A : the group in which the dura was sutured directly, and it accounted for 18.8% Group B : the group in which the dura was not sutured, but a serge cell or a fat or muscle piece was placed, and it accounted for 17.39% Group C : which is the group that was sutured with a fat or muscle graft, and it constituted 49.4% . We evaluated the patients according to the main indicators, which is the occurrence of cerebrospinal fluid hemorrhage during the first six weeks of surgery, which occurred in groups A, B and C at rates of 7.7%, 18.8% and 8.8%, respectively.They were also monitored by secondary indicators such as the average surgical time in minutes, for group A (120) minutes, for group B (90) minutes, and for group C (140) minutes. As for the recovery time for groups A, B and C, it was (8.9, 15.4 and 11.6) U, respectively.We also monitored the secondary complications that occurred in groups A, B and C at rates of 7.7%, 4.5% and 5.9%, respectively. And we concluded from the study that the three methods of managing dura rupture are successful with minor differences between them without significant sequelae.